Analysis of Traders' Social Strategies to Maintain Businesses Perceptions of Islamic Business Ethics - Nafilah, Siti Kholizatun; Qamariyah, Mayzalatul; Fitriani, Nia (Asian Journal of Law and Islamic Finance, 2026)
This study aims to analyze the social strategies applied by traders in Tamidung Village in maintaining their businesses based on the perspective of Islamic business ethics. In Islam, business activities are not only profit-oriented, but must also uphold the values of justice (al-’adl), honesty (sidq), responsibility (amanah), and helpfulness (ta’awun). This study uses a qualitative approach with interview and observation techniques of eight local traders. The results show that merchants apply social strategies such as building local networks, flexibility with debt, friendly service, separation of personal and business finances, and taking advantage of religious momentum to build customer loyalty. Emotional strategies such as closeness and empathy for consumers are also important factors. All of these strategies reflect the principles of Islamic business ethics in real practice, although they have not been supported by adequate recording systems and technological innovations. This study concludes that the success of micro enterprises depends not only on economic capital, but also on the strength of social and spiritual values inherent in daily trading activities.